About the «genic marvel-code» in novel in verse «Divohray» by Olesya Omelchenko (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article emphasizes the problem of spirituality as the most necessary factor in the development of sovereign Ukraine in the historical and philosophical fantastic essay-novel in verses "Divohrai" by O. Omelchenko. The work idealizes human relations at the social and ethical level, artistically interprets the outstanding events and the archaic layers of beliefs of the Ukrainian people as a magical and spiritual power. The author recreates the most ancient layers of historical and cultural memory.
Keywords: problem; spirituality; novel in verse; folklore; customs and traditions